Hydrodynamic Conditions Effects on Soft-Bottom Subtidal Nearshore Benthic Community Structure and Distribution. (30th January 2020) - Foulquier, Clémence; Baills, Julien; Arraud, Alison; D'Amico, Frank; Blanchet, Hugues; Rihouey, Didier; Bru, Noëlle
Abstract : This study assesses the impacts of wave action and freshwater outflow on soft-bottom benthic macrofauna spatial distribution and temporal stability along the highly exposed French Basque coast. Sediment characteristics and macrofauna abundance have been seasonally investigated during two years for nine stations located at the same (6 m) depth and spread over three subtidal sites showing distinct exposure levels. Wave climate has been determined through an operational numerical model. A total of 121 taxa were recorded, gathered in three main faunal assemblages, as revealed by classification and ordination methods. Non-parametric multivariate multiple regression (distance-based linear model) showed that the variations in macrofaunal distribution can be explained by hydrodynamic conditions. Wave exposure strongly linked to estuarine inputs were the most relevant abiotic factors influencing distributional patterns and functional structure as described by biological traits analysis. Despite the influence of these abiotic variables affecting sedimentary dynamics, seasonal stability was observed in macrobenthic assemblages composition suggesting an ability to recover from natural disturbances such as (e.g.) winter storms. In this way, these results provide baseline knowledge for future ecosystem and resource management in shallow subtidal areas strongly exposed to swell and freshwater outflow where soft-bottom macrozoobenthic communities are less frequently studied.